104k views
1 vote
Given the function f(x) = 3 (x - 9) + 6 which of the following represents f-1 (x)?

Given the function f(x) = 3 (x - 9) + 6 which of the following represents f-1 (x)?-example-1

1 Answer

5 votes

Answer:


f^(-1)(x) =
(1)/(3) x + 7

Explanation:

let y = f(x) and rearrange making x the subject, that is

y = 3(x - 9) + 6 ← distribute and simplify right side

y = 3x - 27 + 6 = 3x - 21 ( add 21 to both sides )

y + 21 = 3x ( divide all terms by 3 )


(1)/(3) y + 7 = x

Change y back into terms of x with x =
f^(-1)(x) , thus


f^(-1)(x) =
(1)/(3) x + 7

User Omarojo
by
5.1k points